Characterological traits of adolescents prone to suicidal behavior - А. Ли; О. Аймаганбетова; М. Рыскулова; Е. Умурзаков; Э. Адилова (Хабаршы. Психология және социология сериясы)
This article is dedicated to the study of certain characterological traits of adolescents prone to suicidal behavior. The issue of researching suicidal behavior is particularly significant for modern Kazakhstan, where official statistics annually show a significant upward trend in the suicide rate among adolescents.